Media Flash Card Picture terhadap Kemampuan Merawat Diri Menggosok Gigi pada Siswa Disabilitas Intelektual - Puteri, Sukma Kustin; Yaum, Lailil Aflahkul; Zusfindhana, Inna Hamida (JOEAI (Journal of Education and Instruction), 2025)
This study aimed to determine the effect of using flashcards on self-care skills, specifically tooth brushing, in children with intellectual disabilities. Flashcards, which demonstrate the sequence of steps in tooth brushing, are expected to help children with intellectual disabilities understand and remember the process more easily. This study used a Single Subject Research (SSR) method with an AB design, involving observation and measurement of subjects' abilities before and after the application of flashcards, using percentage calculations. The results showed a positive trend and change in levels with 0% overlap, indicating that the use of flashcards can improve children's ability to brush their teeth independently, with significant improvement from the baseline to the intervention phase. The conclusion is that flashcards have a positive effect on improving self-care skills in tooth brushing among children with moderate intellectual disabilities, and recommendations are provided for further development of visual learning media in special education.   Keywords: Intellectual Disability, Flashcards, Tooth Brushing